THE IMPORTANCE AND EFFECTIVENESS OF RESURSTEJAMKOR TECHNOLOGY FOR GROWING VEGETABLE CROPS IN A GREENHOUSE (Scientific journal of the Fergana State University, 2025)
This article analyzes the importance and effectiveness of resource-intensive technologies in growing vegetable crops in a greenhouse. Resurstejamkor technologies, including hydroponics and aeroponics methods, offer advantages such as food security, water conservation, and climate change adaptation. With the help of these technologies, the yield of vegetable crops increases, and environmental safety is ensured. The article shows the possibilities of sustainable agricultural development through innovative solutions.